Verbal aspect in SLA – Much More than (just) Grammar - Novak Milić, Jasna (2012)
Both L2 students and teacher are well aware of the fact that verbal aspect is one of the most difficult issues to master in Slavic languages. The reason for this is mainly its complexity. Verbal aspect may appear to be a grammatical issue (morphological and syntactical) but it is much more than that. To master verbal aspect in Croatian, learning verbal forms, i.e. the difference between imperfective and perfective verbs, is just the first step. Verbal aspect is just as much a semantical and pragmatical issue as it is a grammatical one. Therefore its proper use requires good general knowledge of a language and a wide knowledge of the world as it is seen through that particular language. Using the examples from Swedish and Croatian, the author will show that linguistic markers are important but often not substantial enough for the proper use of verbal aspect in Croatian. She will present “traditional” approaches to the verbal aspect in Croatian as L2 and try to give an insight into approaches that still need to be developed which are based on the fact that verbal aspect cannot be properly learned/acquired unless it is taught on all levels. The influence of L1 on the acquisition of verbal aspect in L2 will also be discussed, i.e. potential markers in L1 that may influence appropriate or inappropriate use of aspect in L2
Projekt MZOS
ENG